Forensic auditing of related party transactions in Zimbabwean banks to avert fraud - Kapesa, Tonderai (Midlands State University, 2017)
The study sought to evaluate the impact of periodically engaging forensic auditors to verify related party transactions in Zimbabwean banks, focusing on financial institutions listed on the ZSE. The study was motivated by the prevalence of bank failures that have been experienced in Zimbabwe between 2009 and 2013, where two banks were placed under curatorship whilst three were closed. The objectives of the study were to examine the nature and extent of related party lending frauds and the financial impact of these frauds, as well as the cost and benefit analysis of engagement of forensic auditors to check on banks’ related party lending limits compliance and health check with regards to non-performing insider loans. A descriptive design was used for the study, with a positivist philosophy. Data was gathered from a cross-section of respondents who included staff from three commercial banks, staff from five auditing and accounting consultancy companies as well as staff from the Reserve Bank of Zimbabwe’s bank supervision and surveillance division. The study concluded that related party lending was a problem in Zimbabwean banks as responses from all concurred that in all the banks that have failed in Zimbabwe, had been affected by non-performing insider loans (related parties loans). The study came up with a number of conclusions which included the use of forensic auditors as well as suggestions that appointments of these forensic auditors be made annually and bank managers and shareholders were also encouraged to ensure high standards of corporate governance and ethical behaviour. The study recommended that the appointment of forensic auditors be considered by institutional investors as well as individual shareholders as a way to safeguard their investments from managers who may grant loans to undeserving related parties.